2019
DOI: 10.3389/fpls.2019.00178
|View full text |Cite
|
Sign up to set email alerts
|

NtMYB4 and NtCHS1 Are Critical Factors in the Regulation of Flavonoid Biosynthesis and Are Involved in Salinity Responsiveness

Abstract: High levels of salinity induce serious oxidative damage in plants. Flavonoids, as antioxidants, have important roles in reactive oxygen species (ROS) scavenging. In the present study, the tobacco R2R3 MYB type repressor, NtMYB4, was isolated and characterized. The expression of NtMYB4 was suppressed by salinity. Overexpression of NtMYB4 reduced the salt tolerance in transgenic tobacco plants. NtMYB4 repressed the promoter activity of NtCHS1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 58 publications
4
59
0
Order By: Relevance
“…Previous studies have shown that flavonoids are powerful antioxidants and are involved in abiotic stress responses (Martinez et al, 2016;Chen et al, 2019). We found that ROS accumulation was decreased in NtMYB12 transgenic tobacco under low Pi treatment ( Figure 5), which was consistent with the FIGURE 7 | Quantification of flavonol concentration and relative transcript levels of majority genes encoding flavonoid biosynthetic enzymes in WT and 35S: NtMYB12 plants under HP and LP conditions.…”
Section: Overexpression Of Ntmyb12 Enhances Plant Resistance To Low Psupporting
confidence: 87%
“…Previous studies have shown that flavonoids are powerful antioxidants and are involved in abiotic stress responses (Martinez et al, 2016;Chen et al, 2019). We found that ROS accumulation was decreased in NtMYB12 transgenic tobacco under low Pi treatment ( Figure 5), which was consistent with the FIGURE 7 | Quantification of flavonol concentration and relative transcript levels of majority genes encoding flavonoid biosynthetic enzymes in WT and 35S: NtMYB12 plants under HP and LP conditions.…”
Section: Overexpression Of Ntmyb12 Enhances Plant Resistance To Low Psupporting
confidence: 87%
“…Flavonoids are an essential type of secondary metabolites, which play a vital role in plants against oxidative damage caused by ROS and MDA during abiotic stress [ 98 ], which help to enhance salt tolerance when accumulated [ 99 , 100 ]. In the current study, we observed the upregulation of four DEGs involved in flavonoid, flavone, and flavonol biosynthesis ( c82620.graph_c0 , c86889.graph_c0 , c87219.graph_c0 , and c67471.graph_c0 ) in V11E0022 under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we observed the upregulation of four DEGs involved in flavonoid, flavone, and flavonol biosynthesis ( c82620.graph_c0 , c86889.graph_c0 , c87219.graph_c0 , and c67471.graph_c0 ) in V11E0022 under salt stress. Previously conducted studies also showed that salt stress induced the flavonoids accumulation in plants and enhanced their quality [ 98 , 101 ]. The physiological results of the current study also showed higher content of flavonoid in V11E0022 under salt treatment in comparison to other counterparts, and this is due to the overexpression of the genes involved in the flavonoid biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences indicated that the binding capacity between MYB DETFs and GS was stronger in Bluemoon than that in Balin, and this could be one of the reasons that promoted N assimilation in GS/GOGAT cycle and enhanced the NUE of Bluemoon in a complex signaling community at low N condition. Previous research have shown that R2R3-MYB TFs possess the features in improving the tolerance of Arabidopsis to abiotic stress [43]. However, the N-mediated mechanisms for these R2R3-MYB TFs in KB warrant in addition exploration.…”
Section: N Metabolism On the Physiological And Molecular Regulation Imentioning
confidence: 99%